Exploring the Practice of Creative Teaching among Islamic Education Teachers in Nigeria: A Survey Study - Aiyetoro, Abdulkareem Idris; Halabi, Auwwal Kabara; Zakariyah, Momnsur Olawale (Journal of Islamic Educational Research, 2024)
Creative teaching makes learning more enjoyable, meaningful, and engaging. It helps students learn beyond memorisation by improving their thinking skills, which allows them to think creatively, make decisions, and justify their decisions to solve problems independently. Thus, practising creative teaching became more significant since the call for shifting the teaching and learning paradigm from traditional to effective and interactive learning to meet the 21st-century educational goals, which aim to prepare competent individuals for the challenges of the information age. Therefore, this paper aims to investigate teachers’ perception of creative teaching, how they implement it in their classrooms, and examine the relationship between their perception and practice of creative teaching in Islamic education. The study employed a survey design with 120 Islamic education teachers participating. The findings revealed high perception and creative teaching practices among Islamic education teachers and showed a significant relationship between teachers’ perceptions and creative teaching practices. These findings support existing studies that emphasise the importance of teachers’ perceptions in shaping their teaching practices. It also highlights understanding, belief, and attitude as crucial factors that can enhance the implementation of creative teaching methods in their classrooms.